Forgiveness: love relationship - Gnudi Beatrice (Journal for Perspectives of Economic Political and Social Integration, 2018)
The article highlights the relationship between forgiveness, relation and love. It is divided in three sections: an experience of forgiveness which took place in Burundi in the ‘90s, an outline of the culture of that country and some theories about forgiveness in the psychological field.